Infrared measurements of several nitrogen species above the South Pole in December 1980 and November-December 1986 - Murcray, F. J.; Murcray, F. H.; Goldman, A.; Murcray, D. G.; Rinsland, C. P. (1987)
This paper reports the results of the determinations of total column amounts of HNO3 for December 1980 and November 1986, and NO and NO2 for November-December 1986, deduced from ground-based high-resolution IR solar absorption spectra recorded from the Amundsen-Scott South Pole Station. The measurements were obtained shortly after the austral spring ozone minimum and define, for the first time, the ambient levels of these nitrogen species immediately following the break up of the polar vortex.